2011
DOI: 10.1038/onc.2011.357
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-binding protein-1 (IGFBP-1) regulates human schwannoma proliferation, adhesion and survival

Abstract: Merlin is a tumour suppressor involved in the development of a variety of tumours including mesotheliomas. Neurofibromatosis type 2 (NF2), a dominantly inherited tumour disease, is also caused by loss of merlin. NF2 patients suffer from multiple genetically well-defined tumours, schwannomas are most frequent among those. Using our in vitro model for human schwannoma, we found that schwannoma cells display enhanced proliferation because of the overexpression/activation of platelet-derived growth factor receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 46 publications
3
36
0
Order By: Relevance
“…Thus FAK/Src are activated downstream of integrins after merlin loss. RNA interference experiments have confirmed that integrin b1 directly functions upstream of FAK, as knockdown of integrin b1 completely abolished IGFBP1 (acting via integrin alpha 5) mediated FAK phosphorylation/activity at Y397 in human schwannoma cells [14]. Furthermore, the nuclear localisation of FAK in schwannoma cells suggests its regulation of proliferation in the cells without merlin [14].…”
Section: Integrins and Related The Rac/pak/jnk Fak/src And Mtorc1 Pamentioning
confidence: 67%
See 4 more Smart Citations
“…Thus FAK/Src are activated downstream of integrins after merlin loss. RNA interference experiments have confirmed that integrin b1 directly functions upstream of FAK, as knockdown of integrin b1 completely abolished IGFBP1 (acting via integrin alpha 5) mediated FAK phosphorylation/activity at Y397 in human schwannoma cells [14]. Furthermore, the nuclear localisation of FAK in schwannoma cells suggests its regulation of proliferation in the cells without merlin [14].…”
Section: Integrins and Related The Rac/pak/jnk Fak/src And Mtorc1 Pamentioning
confidence: 67%
“…It has been described that activated Src recruits FAK and Paxillin in NF2 À/À mouse astrocyte cells [35]. In addition, both Src activity (Y416) and FAK phosphorylation at Y397 and Y925 (Src phosphorylation site) are significantly increased in schwannoma cells compared with Schwann cells [14,33]. Thus FAK/Src are activated downstream of integrins after merlin loss.…”
Section: Integrins and Related The Rac/pak/jnk Fak/src And Mtorc1 Pamentioning
confidence: 77%
See 3 more Smart Citations